Does bowel cancer screening detect colorectal cancers at an earlier stage?. (13th March 2011) - Patel, P; Pirani, T; Leicester, R; Bouwer, M; Poullis, A
Abstract : Introduction: The NHS bowel cancer screening program (NHS BCSP) currently screens persons between the ages of 60 and 69 for bowel cancer with the aim to detect early cancer and reduce colorectal cancer (CRC) mortality. The inclusion age is currently being extended to 74. The NHS BCSP began in 2006 in England and Nationwide coverage was achieved in 2010. Individuals are invited biennially to provide a stool sample for faecal occult blood test (FOBt) analysis. Bowel cancer usually presents once symptoms occur and as a result at an advanced stage (Duke's stage at diagnosis A 11% vs C/D 54%1 ). Pilot studies of the NHS BCSP showed a reduction in the stage of cancer at diagnosis (Duke's stage at diagnosis (42% stage A, C/D 28.2%2 ). This abstract examines whether the introduction of the NHS BCSP has a real-life effect on stage of CRC at diagnosis in patients from a large screening centre. Methods: Data from BCSP patients from January 2007 to December 2009 were obtained from the database at the South West London BCS centre based at St. Georges'. Data on non-BCSP patients from January 2003 to December 2007 was obtained from local cancer network databases. Results: The table below shows the numbers of cancers and their stage at diagnosis for both patient groups. A higher proportion of Duke's A CRC are diagnosed in patients through the BCSP (43% vs 13%; p<0.05 c 2 test). 26 cancers in the BCSP were in fact polyp cancers which have been included in the Duke's A group. Conclusion: Our results are in keeping with previous pilot data2 and a previously presented abstract3 and show that the BCSP detects CRC at a relatively earlier stage compared to non-BCSP patients. This study needs to be repeated at intervals to see whether this difference changes with further BCSP rounds.